The Balance of Organic and Inorganic Fertilizers to Limiting Factors Nutrient, Soil Fertility and Maize (Zea mays L) Yield on Paddy Soil of C-Excavation - Slamet Minardi; Sri Hartati; Pardono (Sains Tanah: Journal of Soil Science and Agroclimatology, 2014)
The activities for other purposes in the paddy soil will cause soil damage and reduce the values of soil productivity. The use of organic fertilizer is one of efforts to recover and rehabilitate the soil, because it is the key to improve its properties. The purposes of this research were to identify the characteristics of the soil (chemical) as a component of soil fertility, nutrition limiting factors and knowing the balance of organic and inorganic fertilizers on the optimum cultivation of maize (Zea mays L) to achieve maximum production. Research was conducted by using Randomized Complete Block Design (RCBD) with single factor: consisting of six treatments, as follows consisted of control, treatment of inorganic fertilizer as recommended, organic fertilizer (manure), and the balance between organic and inorganic fertilizers. The results showed that the balance between organic and inorganic fertilizers can increase nutrition limiting factors (N and P) and soil fertility in paddy soil of C-excavation. It has been proved by the increasing growth and yield of maize, such as plant height, fresh and dry weight of plant, weight and girth of cob. The highest yield of maize was shown in weight cobs per plant, i.e 190 g as shown in the treatment of the balance between organic and inorganic fertilizers (75: 25)%. It is significantly different than the control treatment, however it showed no significant difference with other treatments.